WAKAF PRODUKTIF DAN PROBLEMATIKANYA DI DUNIA PESANTREN - Achmad Siddiq (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2011)
Productive waqf is a new paradigm introduced in several regulations of endowment in Indonesia. This paradigm requires the management of waqf assets to be more productive, including “pesantren” as an institution that possesses numerous areas of waqf. This situation leads to various problems at pesantren institutions to implement the paradigm of productive waqf. The problems are related to the problems of public ownership to waqf asset, asset status, and legal persons of waqf especially in the sense of the competence and professionalism of nazhir at pesantren.